PENGARUH PENERAPAN METODE BERMAIN PERAN DALAM PELAJARAN BAHASA INDONESIA TERHADAP KEMAMPUANBEKERJA SAMA SISWA DI SDN 112 BELAJEN KABUPATEN ENREKANG - Wahda, Wahda (Pascasarjana Universitas Negeri Makassar, 2018)
this research aims to know the description of the application of the method of playing a role in the Indonesia language learning in ELEMENTARY SCHOOL, to know the description of the capabilities of the cooperation of students, and to find out whether there is influence of the application of the method of play the role of language learning in Indonesia against the cooperation ability of students. This type of research is one group pre test post test. The results showed that (1) the application of the method of playing a role in the language learning Indonesia in SD Negeri Belajen 112 Regency Enrekang done with three stages, namely the preparation and Instruction/activity early, dramatic actions and discussions as well as evaluation of role playing. Where the provision of the application of role playing can be run well. (2) the ability of the student's cooperation is at a very good category. (3) the application of the method of playing a role in language learning ability against Indonesia cooperate very influential because students viewed from the data obtained from experimental groups prior to the implementation of treatment students are on either category While after treatment assessment criteria column on the cooperation of students within the category of very good and with the average value of the good.